To solve this expression, we need to follow the order of operations (PEMDAS).
First, we need to simplify the exponents. Any number raised to the power of 0 is equal to 1.
(-33)^0 = 1
Therefore, the first part of the expression becomes 1.
Next, we need to simplify the parentheses.
8 - 27^0 = 8 - 1 = 7
Now we have:
(-33)^0 + 3/2 * 7
Next, we need to simplify the multiplication:
3/2 * 7 = 21/2
Now we have:
(-33)^0 + 21/2
Finally, we add the two terms together:
(-33)^0 + 21/2 = 1 + 21/2
Adding these fractions requires a common denominator. The common denominator of 2 and 1 is 2.
1 + 21/2 = 2/2 + 21/2 = 23/2
So the simplified value of the expression is 23/2.
9.(-33)^0+3/2(8-27^0
1 answer